Status Gizi Atlet Bola basket POPDA Kota Surabaya: Nutritional Status of Surabaya City POPDA Basketball Athletes - Ragil, Ragil Ar Rasyid; Hariyanto, Agus; Widodo, Achmad (JSH: Journal of Sport and Health, 2024)
The problem of this research is to find out the nutritional status of POPDA Surabaya City Men's basketball athletes. This study aims to examine the nutritional status of POPDA Surabaya City Men's basketball athletes. The research method used is a descriptive survey method with data collection through observation, interviews, and documentation. Height and weight measurements are carried out to determine the body mass index (BMI) of athletes. The population and sample of this study are all Surabaya City POPDA Male players, as many as 12 people, and using a total sampling. The results showed that most athletes, namely 75.0% (9 people), had normal nutritional status. A total of 15.0% (2 people) were classified as thin (mild level of underweight), 10.0% (1 person) were classified as obese (mild excess level of weight), and no athlete had a very obese nutritional status (severe excess weight). The maximum BMI value obtained was 75.0, and the minimum value was 10.0, with an average of 33.33 and a standard deviation of 29.52. The conclusion of this study shows that most athletes have good nutritional status, which is important for supporting the fitness, health, and achievement of athletes